The Role of The Sharia Supervisory Board (DPS) in Supervision of Shariah Compliance in BMT East Java - Moch. Khoirul Anwar; Wakhidah Nur Rohmatul Laili; Moh. Farih Fahmi (Universitas Muhammadiyah Surabaya, 2022)
In carrying out its duties and responsibilities, DPS is required to comply with sharia provisions in order to maintain the stability and existence of BMT. The purpose of this study is to reveal the role of DPS in supervising sharia compliance with managers and implementation of BMT management. This type of research uses field research with a qualitative approach. The type of data used is primary data through the responses of 13 DPS spread across East Java. The results of the study found that the majority of DPS did not fully understand the concept of sharia compliance according to the DSN-MUI fatwa so that the supervision carried out by DPS had not run optimally.